TABLIGHI JAMAAT SCHISM: RESPONSES AND CHANGES OF ITS MEMBERS IN INDONESIA - Achmad Achmad (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2021)
This study is an analysis of the Tablighi Jamaat schism in India, various responses, and changes that have occurred to its members in Indonesia. Using a socio-anthropological and historical approach, the results of this study show that the schism that occurred was caused by the conflict over the struggle for the highest authority of the movement of its leaders in India. The fragmentation after the death of In'mul Hasan further sharpened the contestation among its senior members, until the Tablighi Jamaat split into two groups. First, those who declared Maulana Sa'ad as their sole leader and identified themselves as the Nizamuddin group. Secondly, those who supported the international Shura system and identified themselves as the Shura 'Alami group. In Indonesia, these two groups are also developing, building demarcation lines from each other, claiming each other as the authenticity of the truth, and carrying out da'wah in accordance with the directions of their respective elders. After the schism, both of them were transformed into a new organizational structure in accordance with the interests of their respective groups.